Dealing with sickness certification - a survey of problems and strategies among general practitioners and orthopaedic surgeons - Nilsson Gunnar; Löfgren Anna; Hagberg Jan; Alexanderson Kristina; Arrelöv Britt; Ponzer Sari (BMC, 2007)
Abstract Background In order to get sickness benefit a sick-listed person need a medical certificate issued by a physician; in Sweden after one week of self-certification. Physicians experience sick-listing tasks as problematic and conflicts may arise when patients regard themselves unable to work due to complaints that are hard to objectively verify for the physician. Most GPs and orthopaedic surgeons (OS) deal regularly with sick-listing issues in their daily practice. The aim of this study was to explore perceived problems and coping strategies related to tasks of sickness certification among general practitioners (GP) and orthopaedic surgeons (OS). Methods A cross-sectional study about sickness certification in two Swedish counties, with 673 participating GPs and 149 OSs, who answered a comprehensive questionnaire. Frequencies together with crude and adjusted (gender and working years) Odds ratios were calculated. Results A majority of the GPs and OSs experienced problems in sickness certification every week. To assess the patient's work ability, to handle situations when they and the patient had different opinions about the need for sickness absence, and to issue prolongation certificates when the previous was issued by another physician were reported as problematic by a majority in both groups. Both GPs and OSs prolonged sickness certifications due to waiting times in health care or at Social Insurance Office (SIO). To handle experienced problems they used different strategies; OSs issued sickness certificates without personal appointment more often than the GPs, who on the other hand reported having contact with SIO more often than the OSs. A higher rate of GPs experienced support from management and had a common strategy for handling sickness certification at the clinic than the OSs. Conclusion Most GPs and OSs handled sickness certification weekly and reported a variety of problems in relation to this task, generally GPs to a higher extent, and they used different coping strategies to handle the problems.